Intravenous AAV9 efficiently transduces myenteric neurons in neonate and juvenile mice - Gombash, Sara E.; Cowley, Christopher J.; Fitzgerald, Julie A.; Hall, Jodie C. E.; Mueller, Christian; Christofi, Fedias L.; Foust, Kevin D. (Frontiers in Molecular Neuroscience, 2014)
Our recent discovery that adeno-associated virus type 9 (AAV9) can cross the blood brain barrier holds promise for the treatment of global neurological disease. Early studies with AAV9 gene therapy focused on transduction within the brain and spinal cord, but intravenous infusion results in widespread vector dissemination. Therapies for neurological diseases with autonomic or gastrointestinal involvement may require global gene expression. Gastrointestinal complications are often associated with Parkinson’s disease and autism. Lewy bodies, a pathological hallmark of Parkinson’s brains, are routinely identified in the neurons of the enteric nervous system (ENS) following colon biopsies from patients. The ENS is the intrinsic nervous system of the gut, and is responsible for coordinating the secretory and motor functions of the gastrointestinal tract. ENS dysfunction can cause severe patient discomfort, malnourishment, or even death as in intestinal pseudo-obstruction (Ogilvie syndrome). Importantly, ENS transduction following systemic vector administration has not been thoroughly evaluated. Here we show that systemic injection of AAV9 into neonate or juvenile mice results in transduction of 25-57% of ENS myenteric neurons. Transgene expression was prominent in choline acetyltransferase positive cells, but not within vasoactive intestinal peptide or neuronal nitric oxide synthase cells, suggesting a bias for cells involved in excitatory signaling. AAV9 transduction in enteric glia is very low compared to CNS astrocytes. Enteric glial transduction was enhanced by using a glial specific promoter. Furthermore, we show that AAV8 results in comparable transduction to AAV9 though AAV1, 5 and 6 are less efficient. These data demonstrate that systemic AAV9 has high affinity for peripheral neural tissue and is useful for future therapeutic development and basic studies of the ENS. Transduction patterns for neurons and glia may differ between ENS and CNS.